2006
DOI: 10.1097/01.mao.0000224083.70225.b7
|View full text |Cite
|
Sign up to set email alerts
|

Change of Phonation Control After Cochlear Implantation

Abstract: As expected, the voice quality of the prelingually deafened children was significantly worse than that of the postlingually deafened adults. After cochlear implantation, the children significantly improved their short-term and long-term F0 and amplitude variability. In adults, no significant improvement was detected. We suppose that the improvement is a consequence not only of the acquired hearing control but also of the adaptation ability of neuromuscular phonation control and the maturing of these control me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
0
21
0
4
Order By: Relevance
“…13,19,20 Another study reported no statistically significant findings on F0 values and their variability after CI in 11 adults. 11 These studies of postlingually deaf adults have mostly addressed aspects of acoustic analysis, placing no emphasis on perceptual evaluation in their results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,19,20 Another study reported no statistically significant findings on F0 values and their variability after CI in 11 adults. 11 These studies of postlingually deaf adults have mostly addressed aspects of acoustic analysis, placing no emphasis on perceptual evaluation in their results.…”
Section: Introductionmentioning
confidence: 99%
“…9 When these patients acquire a hearing impairment at some point in life, however, they can develop vocal changes because of the lack of monitoring provided by auditory feedback. 8,10,11 Auditory feedback may be provided by the use of auditory prosthetics devices (hearing aids). However, children or adults with severe or profound hearing loss will often not benefit from hearing aids.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, indivíduos com alterações no sistema auditivo, principalmente nos casos em que a perda auditiva é classificada como severa e profunda, podem apresentar aumento da média de f 0 e não ouvir a própria voz em decorrência da ausência de feedback auditivo 2 . As características vocais podem variar de acordo com o grau da perda auditiva, o tipo de dispositivo eletrônico utilizado, a idade de adaptação do aparelho de amplificação sonora individual (AASI) ou ativação do implante coclear (IC), bem como dependendo do período em que a perda auditiva ocorreu, pré ou pós-lingual 3 .…”
Section: -Critérios De Inclusão E Exclusãounclassified
“…According to Teston [21], this is one of the best indicators, along with shimmer, of the recovering of hearing perception, being one of the parameters that continues to present several differences in relation with normality [22,23]. We find authors [15,20] who state that jitter is one of the parameters that most immediately reaches the values of normality after implantation. Van Lierde et al [23] compared this parameter in subjects using hearing aids (n = 6) or implants (n = 9) and determined that hearing aid users presented jitter values higher than normality (jitt = 0.76%), whereas implant users presented diminished values for the same parameter (jitt = 0.33%).…”
mentioning
confidence: 91%
“…Other authors state that, after previous studies, the F 0 parameter was about 20% higher in deaf children [16] or that F 0 increased when children stopped receiving hearing feedback with the cochlear implant [17,18]. Other authors, however, have not detected significant improvement in F 0 values despite the use of the implant [11,19,20].…”
mentioning
confidence: 93%